REDUCING THE BURDEN ON THE STATE BUDGET AND ATTRACTING PRIVATE SECTOR FUNDS IN THE FINANCING OF FORESTRY IN UZBEKISTAN - Mamatkulova Mukhlisa Mamirzhanovna (European Science Publishing, 2025)
This article explores ways to reduce the fiscal burden on Uzbekistan’s state budget in financing forestry by attracting private sector funds. Based on international experience and local analysis, the paper proposes blended financing models and incentive mechanisms to improve financial sustainability in the sector.
Keywords: Forestry finance, public-private partnership, green bonds, carbon credits, fiscal sustainability, Uzbekistan, ecosystem services.